The Necessity of Learning about the History of EFL to Teach it Case of: Third Year LMD Students of English at the University of Souk-Ahras. - LADJENEF, Hadda (My University, 2023)
Abstract The present paper aims to confirm the necessity of learning about the history of EFL to teach it at Souk-Ahras University. The main concern of the current study is that learning about the history of EFL is not necessary in order to teach English. So, they cannot teach effectively. It hypothesizes that EFL learners and teachers will teach English effectively, if they learn about the history of EFL. Thus, the work attemps to confirm the necessity of learning about the history of EFL to teach it. In the process of achieving the above objectives, this research depends on the mixed method; quantitative and qualitative. Quantitative is delivered to third year students of English at Mohamed CherifMessadia Souk-Ahras. Qualitative is interview with teachers to confirm if learning about the history of EFL is necessary to teach it. ------------ الملخص تهدف الورقة الحالية الى تاكيدضرورة التعرف على تاريخ اللغة الإنجليزية كلغة اجنبيةلتدريسها في جامعة سوق أهراس. الشاغل الرئيسي للدراسة الحالية هو إن التعرف على تاريخ اللغة الإنجليزية كلغة أجنبية ليس ضروريًا لتدريس اللغة الإنجليزية. لذلك هملا يستطيع التدريس بشكل فعال. وهي تفترض أن متعلمي اللغة الإنجليزية كلغة أجنبية سيقومون بالتدريساللغة الإنجليزية بشكل فعال، إذا تعلموا عن تاريخ اللغة الإنجليزية كلغة أجنبية. وهكذا، يحاول العملاللغة الإنجليزية بشكل فعال، إذا تعلموا عن تاريخ اللغة الإنجليزية كلغة أجنبية. وهكذا، يحاول العمللتحقيق الأهداف المذكورة أعلاه، يعتمد هذا البحث على الطريقة المختلطة.كميا ونوعيا. يتم تسليم الكمية لطلاب السنة الثالثة من اللغة الإنجليزيةفي محمد شريف المساعدية سوق أهراس. النوعية هي مقابلة مع المعلمين لتأكيد ما إذا كان التعرف على تاريخ اللغة الإنجليزية كلغة أجنبية ضروريًا لتدريسها. -------------- Résumé Le présent article vise à confirmer la nécessité de connaître l'histoire de l'EFL l'enseigner à l'Université Souk-Ahras. La principale préoccupation de l'étude actuelle est que l'apprentissage de l'histoire de l'EFL n'est pas nécessaire pour enseigner l'anglais. Afin qu'ils ne peut pas enseigner efficacement. Il suppose que les apprenants EFL enseigneront Anglais efficacement, s'ils apprennent l'histoire de l'EFL. Ainsi, le travail tente de confirment la nécessité de connaître l'histoire de l'EFL pour l'enseigner. Dans le processus d'atteindre les objectifs ci-dessus, cette recherche dépend de la méthode mixte; quantitatif et qualitatif. Quantitative est délivrée aux étudiants de troisième année d'anglais à Mohamed Cherif Messadia Souk-Ahras. Le qualitatif est un entretien avec les enseignants pour confirmer si l'apprentissage de l'histoire de l'EFL est nécessaire pour l'enseigner.